Enhanced hydrogenation activity and diastereomeric interactions of methyl pyruvate co-adsorbed with R-1-(1-naphthyl)ethylamine on Pd(111) - Mausumi Mahapatra (Nature Portfolio, 2016)
Achiral sites on a catalyst can result in formation of racemic product, though this can be avoided where the chiral sites lead to enhanced reaction rates. Here, the authors report that for the hydrogenation of methyl pyruvate the chiral modifier enhances the hydrogenation reactivity by favouring the more reactive enol tautomer.